Improved life cycle performance of mechanical ventilation systems. (CIBSE, 2003)
Introduces designers to the performance standards for air conditioning and mechanical ventilation systems originating from Part L (2002). It will benefit anyone who wants to obtain a reliable prediction of costs of ownership of a ventilation system. It will be highly relevant to PFI bidders and to owners of systems.
"Dti, Department of Trade and Industry."
"Registered charity number 278104"--Title page verso
Includes index.
Keywords: Ventilation -- Design and construction.; Air conditioning -- Efficiency.; Air conditioning equipment industry -- Quality control.; Heating -- Specifications.; Ventilation -- Specifications.; elektronické knihy; electronic books